A history of advertising the first 300,000 years - Richards, Jef I. (Rowman & Littlefield, 2022)
"This full-color book offers a sweeping history of advertising. It places developments in the advertising and marketing industries within a framework of major cultural events to help readers understand the conditions under which advertising developed. Timelines of historical and advertising industry events begin each chronological section"--